Penerapan Fungsi Manajemen pada Gerakan Dakwah di Pimpinan Daerah Muhammadiyah (PDM) Kota Medan - Tanjung, Yudha Ferdiansyah; Ritonga, Hasnun Jauhari (Wardah, 2023)
The function of da'wah management consists of 4 (four) functions, namely takhthith, thanzim, tawjih, and riqobah. Muhammadiyah has a da'wah movement that is carried out in accordance with the Muhammadiyah Regional Leadership (PDM) of Medan City which is one of the structural Muhammadiyah organizations appointed in accordance with the congress formed based on previous Muhammadiyah deliberations. The da'wah movements carried out by PDM Medan City are: a) da'wah bil lisan; b) da'wah bil hal; c) da'wah bi tadwin; d) da'wah bil hikmah. The application of the management function to the cultural da'wah movement carried out by the Muhammadiyah Regional Leadership of Medan City is applied by paying attention to the cultural da'wah approach. The management function refers to takhtith (da'wah planning) where Muhammadiyah previously conducted deliberations and then would lower the decision to carry out how to da'wah, thanzim (organizing da'wah) where this organization is adjusted to the existing organizational structure, tawjih (driving da'wah), namely the implementation of da'wah that has been decided or planned in deliberations then realized, finally riqobah (control and evaluation of da'wah), namely supervision carried out on da'wah is carried out so that there is no confusion in da'wah.